Prioritizing emergency management phases in elementary schools: A case study using technique for order of preference by similarity to ideal solution (TOPSIS) - Adlin Adriana, Zulkipli; Diannita, Rindang; Al Khowwas, Ibrahim; Mohd Najib, Yacob; Azizan, Ramli (Universiti Malaysia Pahang, 2025)
Emergency management is critical to ensuring the safety and well-being of students, teachers, and staff in educational institutions. The purpose of this study is to prioritize the emergency management phases of mitigation, response, preparedness, and recovery in three selected elementary schools, with a focus on fire incidents. The method used is The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The result showed that School 2 prioritized a robust response strategy due to its central city location, while School 1 focused on mitigation because of its proximity to a fire station. School 3 emphasized preparedness, given its rural location and predominantly low-income student population. The study's findings underscore the importance of tailored strategies for educational institutions, emphasizing response strategies and preparedness.